2017
DOI: 10.3233/mnm-16118
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to investigate energy intake and food frequency among middle aged and elderly people in Mauritius

Abstract: Middle age is an important period of life whereby unhealthy eating habits may develop. In addition, during old age, certain transitions such as retirement may impact on eating habits and health. This study was undertaken to identify and characterize dietary patterns in the middle aged and elderly people and to assess different factors influencing energy intake. A total of 500 participants aged between 35-65 years old completed a self-reported questionnaire investigating the eating habits, Physical Activity Lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…A score of 1 was assigned for a right answer and a score of 0 for a wrong answer and "don't know". 14 Section IV: Anthropometric measurements Physical measurements, including weight and height were obtained using the same tools to reduce the possibility of errors. A measuring tape and ruler was used to measure the height and the participant stood bare foot with the head horizontal against the wall.…”
Section: Frequency Scorementioning
confidence: 99%
See 3 more Smart Citations
“…A score of 1 was assigned for a right answer and a score of 0 for a wrong answer and "don't know". 14 Section IV: Anthropometric measurements Physical measurements, including weight and height were obtained using the same tools to reduce the possibility of errors. A measuring tape and ruler was used to measure the height and the participant stood bare foot with the head horizontal against the wall.…”
Section: Frequency Scorementioning
confidence: 99%
“…However, this alone is insufficient to account for the socioeconomic inequalities in obesity. 14 There is an interrelationship between physical exercise and energy intake because physical activity has the capacity to alter energy expenditure, and when done repeatedly, leads to either weight loss or the requirement to increase energy intake. 11 A study showed that there is insufficient data to support the recommendation that physical activity may help to mitigate the decline in appetite and energy intake that happens as people age 15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Recent studies have focused on issues such as BMI , PAL , energy intake, nutrition intervention programs and different target population. 16,17,18,19,20,21,22,23,24,25,26,27,28 However, no study has been conducted to evaluate the influence of SD consumption on BMI and energy intake among adults.…”
Section: Introductionmentioning
confidence: 99%